Impact of interventional and non-interventional variables on anthropometric long-term development in glutaric aciduria type 1: a national prospective multi-centre study - Märtner, E.M. Charlotte; Maier, Esther M.; Mengler, Katharina; Thimm, Eva; Schiergens, Katharina A.; Marquardt, Thorsten; Santer, René; Weinhold, Natalie; Marquardt, Iris; Das, Anibh M.; Freisinger, Peter; Grünert, Sarah C.; et al. (Journal of inherited metabolic disease, 2021)
Glutaric aciduria type 1 (GA1) is a rare neurometabolic disorder, caused by inherited deficiency of glutaryl-CoA dehydrogenase, mostly affecting the brain. Early identification by newborn screening (NBS) significantly improves neurologic outcome. It has remained unclear whether recommended therapy, particular low lysine diet, is safe or negatively affects anthropometric long-term outcome. This national prospective, observational, multi-centre study included 79 patients identified by NBS and investigated effects of interventional and non-interventional parameters on body weight, body length, body mass index (BMI) and head circumference as well as neurological parameters. Adherence to recommended maintenance and emergency treatment (ET) had a positive impact on neurologic outcome and allowed normal anthropometric development until adulthood. In contrast, non-adherence to ET, resulting in increased risk of dystonia, had a negative impact on body weight (mean SDS −1.07; P = .023) and body length (mean SDS −1.34; P = −.016). Consistently, longitudinal analysis showed a negative influence of severe dystonia on weight and length development over time (P < .001). Macrocephaly was more often found in female (mean SDS 0.56) than in male patients (mean SDS −0.20; P = .049), and also in individuals with high excreter phenotype (mean SDS 0.44) compared to low excreter patients (mean SDS −0.68; P = .016). In GA1, recommended long-term treatment is effective and allows for normal anthropometric long-term development up to adolescence, with gender- and excreter type-specific variations. Delayed ET and severe movement disorder result in poor anthropometric outcome.
First published: 03 December 2020
Gesehen am 03.12.2021